Accuracy assessment on underground utility equipment / Oliver Hoon Leh Ling (Ed.) … [et al.] - Hoon, Oliver Leh Ling (Ed.); Saifuddin, Khadijah; Othman, Ainon Nisa; Razali, Mohamad Hezri; Khalid, Nafisah (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
This paper discusses about the accuracy and capability of underground utility equipment which is Ground Penetrating Radar (GPR) and Electromagnetic Locator (EML). The study area is located at JUPEM Underground Utility Detection Equipment Calibration Laboratory, Jalan Sultan Yahya Petra Kuala Lumpur. This study focused on accuracy, consistency and reliability of the both equipment due to the density of development especially in urban city areas poses new obstacles to new development which is the conflict of space. These issue raises when a new particular infrastructure needs to deploy in the same area with the crowded underground utilities. Here, the process of installation works for underground utilities need to be conducted carefully in order to avoid any utility accidents and casualties by determining the exact position and alignment of the existing underground utility. The common and the best option in the determination of any underground facilities are by underground utilities survey emphasized with buried objects which need to know the location installed and the depth deployed to ensure the safety of any development up coming. There are several methods with using different types of instruments include GPR, EML, Seismic Boom and Buried method. Thus, this paper is carried out for determining the accuracy of depth values obtained from GPR (Mala ProEx) and EML (RD8000) which are based on radar and electromagnetic concept respectively. Based on the result and analysis, it can be concluded that the accuracy achieved from GPR (Mala ProEx) is better compared with EML (RD8000). It has been proved by statistical data analysis in which the Root Mean Square Error (RMSE) values from GPR Mala ProEx for line A, line B and line C is smaller with millimeter level accuracy (3mm – 8mm) compared to EML RD8000 with centimeter level accuracy (18cm – 43cm). In term of reliability of dataset for the both types equipment for underground utility mapping, it shows that the range value of depth for all the types of utility is not significantly diverse. Fifty-six percent (56%) with centimeter level accuracy and Fourty-four percent (44%) with millimeter level accuracy.